Co-creation and online learning: A case study of online discussion boards at an English business school. (5th February 2018) - Stoten, David William; Oliver, Stanley; O'Brien, Jim; Swain, Callum Garland
Abstract : Purpose: The purpose of this paper is to explore how students interact with discussion boards, given different cultural backgrounds. The paper draws from the literature on activity theory, communities of practice, as well as learning theory to inform a discussion on students use of discussion boards. Design/methodology/approach: Students from a range of nationalities studying in London were issued with a five-point Likert scale questionnaire that was supplemented with opportunities for students to elaborate on their thoughts through the use of open response comment boxes. In addition to qualitative analysis, statistical analysis using the Kruskal-Wallis test was undertaken to investigate the degree to which national background influenced the use of discussion boards. Students were divided into four groups (British, European, Asian and African) for the purpose of analysis. Findings: The findings tentatively echo earlier work (Hofstede) on how cultural/national factors impact on how people approach work/study. In this case, differences between African and Asian students were most apparent in a number of interesting areas. Research limitations/implications: This study is limited by the sample size and time constraints involved. The data were drawn from 70 students. Future student intake will be added to this cohort to build up the sample and test preliminary findings. Practical implications: This paper infers that teachers should be actively aware of how nationality/cultural background may impact on how students learn and engage with information technology during the learning process. Originality/value: This paper contributes to the work on learning in diverse learning communities and how information technology can contribute to a learning community.